PERSEPSI WISATAWAN MANCANEGARA TERHADAP KUALITAS OBJEK DI CANDI PRAMBANAN SLEMAN YOGYAKARTA - , KARTIKA F. NIEAMAH; , Dr. Ir. Djoko Wijono, M.Arc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Prambanan is the largest Hindu temple complex in Yogyakarta. Prambanan temple is one of the Yogyakarta tourism icons. In 1991, this temple is a cultural heritage site recognized by UNESCO. This case be the main attraction for foreign tourist. Therefore, the manager should pay attention to the quality of the existing object in the Prambanan temple. This study aims to analyze and describe the foreign tourist perception before visiting and to analyze and describe the tourist perception on the quality object of Prambanan temple to determine the market demand. The method used is qualitative by linking three variables, ie before visiting perception, expectation and perception on the object quality variabel. Technique for taking data on the tourist perception before visiting and expectation are using in-depth interview to the tourist who visit, while in the perception of object quality is using in-depth interview to the tourist who visit, interviewing the manager and observation. I conducted in-depth interview on perception of data analysis before visiting, while in the tourist perception of object quality conducted-depth interview, observation and documentation. The process of data analysis is data collection (in-depth interviews, observations, documentation) then conducted data reduction, coding in accordance with the parameters and indicators and interpretation. Validity test is conducted by using source triangulation. The results showed that the perception of tourists before visiting is Prambanan temple is beautiful, has a unique architecture, and has an interesting history. The motivation is need of curiosity. The expectation is hoping to see the grandeur of the temple, to study the difference of Hindu and Buddhist architecture, hoping the temple that will be seen will be greater than imagined, and can see the huge temple complex. While perceptions after visiting is has very high historical value, has an interesting legend, Prambanan temple has huge temple complex despite many temples were missing but does not reduce the beauty, the architecture has a very unique and interesting, Prambanan temple complex is well organized. Prambanan temple is also safe, comfortable, clean, beautiful like a city park. Thereby, comparison of tourist perception and expectation before and after visiting is appropriate or even exceed the expectation.